Responses of terrestrial plants and invertebrates to environmental change at high latitudes - Callaghan, Terry V.; Sonesson, Mats; Sømme, Lauritz; Walton, D. W. H.; Christensen, T.; Block, W. C.; Drewry, D. J.; Laws, Richard Maitland; Pyle, John Adrian (Philosophical Transactions of the Royal Society of London. Series B: Biological Sciences, 1997)
Many invertebrates show flexibility in their life cycles and are likely to respond to changes in climate as they have in the past. However, changes in temperature and photoperiod may disturb the life cycles of some existing polar invertebrates while continuing to constrain the polewards migration of more temperate species. Higher plants are likely to have higher productivity as temperatures and atmospheric CO2 levels increase but this productivity will be reduced by exposure to increasing UV-B radiation. Higher plants migrate more slowly than the rate at which climate is predicted to change and many species will be trapped in supra-optimal climates. Both mosses and lichens can migrate faster than higher plants, propagules of non-polar species already reaching the Antarctic, but they have fewer mechanisms of responding to changing environments. Polar vegetation and ecosystems provide feedback to the climate system: positive feedbacks are associated with decreases in reflectivity and increased carbon emissions from warm ing soils. In the Antarctic, feedback and responses to environmental change will be smaller than in the Arctic because of the less responsive cryptogams which dominate the Antarctic, the paucity of Antarctic soils, and geographical barriers to plant and invertebrate migrations.
Publisher: Royal Society
Keywords: Antarktis; biologi; botanikk; klimaendringer; lav; moser; virvelløse dyr

Anhydrobiosis and cold tolerance in tardigrades - Sømme, Lauritz (European Journal of Entomology, 1996)
A review of the literature regarding anhydrobiosis and cold tolerance in tardigrades is presented. During increasing desiccation, invertebrates like tardigrades, rotifers, nematodes and some collembolans are able to shut down metabolism to undetectable levels. When tardigrades are entering anhydrobiosis, a tun-like structure is formed, facilitated by structural adaptations of the cuticle. Slow dehydration is essential for tun formation, and the accumulation of trehalose during this process may help to stabilize phospholipids and proteins. Wax extrusion on the cuticle surface reduces transpiration. A fraction of 5-15% of the initial body water is retained during anhydrobiosis. Tardigrades are principally aquatic organisms, but anhydrobiosis makes it possible for some species to live in habitats with changing moisture conditions. Tardigrades in anhydrobiosis may tolerate exposure to freezing temperatures of liquid gases, and some species also survive such temperatures in their hydrated state. Few investigations are available on the relation of tardigrades to temperatures more representative to their natural environments. Experimental studies, however, from Greenland and the Antarctic Continent suggest that some species overwinter both in a hydrated frozen state and in anhydrobiosis. During the summer, a number of tardigrade species have been recorded from cryoconite holes, formed on the surface of glaciers. These species are freeze tolerant since their habitats are permanently frozen during the winter.
Keywords: Antarktis; Dronning Maud Land; biomonitorering; bjørnedyr; entomologi; kuldetoleranse; polarområdene; virvelløse dyr

Invertebrates in Hot and Cold Arid Environments - Sømme, Lauritz (Springer-Verlag, 1995)
Keywords: Antarktis; forskning; kuldetoleranse; virvelløse dyr

Cold tolerance in Tardigrada from Dronning Maud Land, Antarctica - Sømme, Lauritz; Meier, Terje (Polar Biology, 1995)
Survival at low temperatures was studied in three species of Tardigrada from Muhlig-Hofmannfjella, Dronning Maud Land, Antarctica. Both hydrated and dehydrated specimens of Echiniscus jenningsi, Macrobiotus furciger and Diphascon chilenense had high survival rates following exposure to -22 degrees C for ca. 600 days, and dehydrated specimens following 3040 days at this temperature. In hydrated E. jenningsi, mortality increased with the duration of exposure from 7 to 150 days at -80 degrees C, while mortalities of the two other species did not change. Hydrated specimens of all species were rapidly killed at -180 degrees C, but all species exhibited good survivorship in the dehydrated state after 14 days at -180 degrees C. In conclusion, hydrated tardigrades are able to survive extended periods at low temperatures, and dehydrated specimens are even better adapted to survive overwintering on Antarctic nunataks.
Keywords: Dronning Maud Land; biologi; biomonitorering; bjørnedyr; kuldetoleranse; virvelløse dyr

Notes on the ecology and physiology of the Antarctic oribatid mite Maudheimia wilsoni - Sømme, Lauritz; Strømme, Alexander; Zachariassen, Karl Erik (Polar Research, 1993)
The oribatid mite Maudheimia wilsoni Dalenius was found to be numerous on the underside of stones at Jutulsessen (72-degrees-S, 3-degrees-E) in Dronning Maud Land, Antarctica. Daily temperature fluctuations of the microhabitat from as high as 19-degrees-C and to as low as -17-degrees-C were observed during the austral summer. Optimal activity of the mites occurred at 10-degrees-C. Even in January the mean supercooling point of adult mites was as low as - 30.8 +/- 4.7-degrees-C. Haemolymph osmolality ranged from 500 to 800 mOsmol and thermal hystersis freezing points from -4.7 to - 6.1-degrees-C. Adult mites had a mean water content of 43.6% and a water loss rate of 0.12 mug h-1 at 15-degrees-C and 10% relative humidity.
Keywords: Dronning Maud Land; NARE 1989/90; entomologi; midder; miter; virvelløse dyr; zoologi; økofysiologi; økologi

Ecophysiological adaptations in mites and collembolans in Dronning Maud Land - Strømme, Alexander (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; midder; miter; virvelløse dyr; zoologi; økofysiologi

Terrestrial arthropods of Bouvetøya - Sømme, Lauritz (Polar Research, 1986)
Keywords: Bouvetøya; ekspedisjoner; forskning; midder; miter; virvelløse dyr

Terrestrial Habitats - invertebrates - Sømme, Lauritz (Antarctica, 1985)
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Terrestrial invertebrates of Mühlig-Hofmannfjella, Dronning Maud Land - Sømme, Lauritz (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; leddyr; virvelløse dyr; zoologi

Cold Hardiness of Terrestrial Mites at Signy Island, Maritime Antarctic - Block, William; Sømme, Lauritz (Oikos, 1982)
The cold hardiness of four species was studied in respect of supercooling ability, cryoprotective substances, chill-coma temperatures and survival under anaerobiosis. The effects of low temperature acclimation and starvation on cold hardiness were examined experimentally. (2) Mean supercooling points of field animals ranged from -6.1° to -28.8°C during Jan-Mar 1980. In Nanorchestes antarcticus (Strandtmann) and Alaskozetes antarcticus (Michael), a bimodal distribution of individual supercooling points occurred with the low group (LG) consisting of animals without gut nucleators. In Stereotydeus villosus (Trouessart) and Gamasellus racovitzai (Trouessart) only a high group (HG) was present in the supercooling-point distributions. (3) In all species, except the predatory G. racovitzai, starvation combined with low temperature exposure for various time periods lowered the mean supercooling point. This was associated with increased concentrations of glycerol in the body fluid. Glucose, ribitol and mannitol together with straight chain hydrocarbons were also detected in the extracts by GLC techniques. (4) Chill-coma temperatures varied from -4.5° to -8.0°C. (5) Under anoxia at 0°C, survival of A. antarcticus was greater than that of G. racovitzai, with the later nymphal stages being slightly more resistant than adults.
Publisher: [Nordic Society Oikos, Wiley]
Keywords: Antarktis; Sør-Orknøyene; entomologi; kuldetoleranse; midder; miter; virvelløse dyr

Supercooling and winter survival in terrestrial arthropods - Sømme, Lauritz (Comparative Biochemistry and Physiology Part A: Physiology, 1982)
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Cold Hardiness of Collembola at Signy Island, Maritime Antarctic - Sømme, Lauritz; Block, William (Oikos, 1982)
The cold hardiness of two Antarctic species of Collembola, Cryptopygus antarcticus Willem and Parisotoma octooculata (Willem), was studied in field fresh, starved and low temperature acclimated specimens at Signy Island, in the South Orkney Islands. Supercooling points of both species clearly fell in a high group (HG) and a low group (LG) with a division at ca. -15°C. Field fresh specimens mainly had HG supercooling points, while starvation at 5° and 15°C greatly increased the number of LG animals. Further evidence of the relation between supercooling and feeding status was obtained in C. antarcticus. Specimens fed moss turf homogenate almost entirely returned to HG supercooling points, indicating the presence of efficient nucleators in this substrate. In specimens fed purified green algae a high proportion of LG supercooling points was retained, which suggests a lack of nucleators in this kind of food. Increased ability of LG specimens to supercool was demonstrated in C. antarcticus following acclimation at -5°C, and in P. octooculata at 0°C. In C. antarcticus an increase in concentrations of cryoprotective substances took place at -5°C concurrent with the lowering of the mean supercooling point. The main substances of the multicomponent cryoprotectant system of this species were trehalose, mannitol and glycerol. Chill-coma temperatures of specimens collected in the field differed in C. antarcticus and P. octooculata with mean values of -8.3° and -4.8°C, respectively. P. octooculata was less resistant to anaerobic conditions than C. antarcticus. All specimens of the former species were killed within 8 d in nitrogen at 0°C, while ca. 30% of C. antarcticus specimens survived after 28 d.
Publisher: [Nordic Society Oikos, Wiley]
Keywords: Antarktis; Sør-Orknøyene; entomologi; kuldetoleranse; leddyr; virvelløse dyr

Cold tolerance of alpine, Arctic, and Antarctic Collembola and mites - Sømme, Lauritz (Cryobiology, 1981)
Because of their dominant role in the fauna of alpine, Arctic and Antarctic locations Collembola and mites are of particular interest regarding adaptations to low temperatures. No freezing-tolerant species have been found in these groups of terrestrial arthropods, and it appears that all species depend entirely on supercooling to survive the lower temperatures of their habitats. While summer animals have high supercooling points, an increase in supercooling ability occurs during autumn and early winter, and can be explained as a two-step process. Initially gut content has to be eliminated to avoid heterogeneous nucleation at high subzero temperatures due to foreign nucleating agents. Second, supercooling is further enhanced through accumulation of glycerol or other lowmolecular cryoprotective substances. Further studies are needed on the ability of such animals to avoid inoculative freezing in their microhabitats.
Keywords: Antarktis; entomologi; kuldetoleranse; midder; miter; virvelløse dyr; zoologi

Supercooling in two Antarctic arthropods from Bouvetøya - Sømme, Lauritz (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Cold tolerance of two Antarctic terrestrial arthropods - Block, William; Young, Stephen R; Conradi-Larsen, Else-Margrete; Sømme, Lauritz (Experientia, 1978)
Two Antarctic arthropods,Alaskozetes antarcticus (Acari) andCryptopygus antarcticus (Collembola) possess the ability to supercool to −30°C, but the realisation of this potential is dependent on starvation. The mite contains glycerol in a concentration of about 1% fresh weight.
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; virvelløse dyr

Cold-Hardiness of Cryptopygus antarcticus (Collembola) from Bouvetøya - Sømme, Lauritz (Oikos, 1978)
Cryptopygus antarcticus Willem were extracted from samples of mosses collected at Bouvetøya during the Norwegian Antarctic Expedition in February 1977. The body length of the collembolans from these samples ranged from 225 to 1125 μm. The collembolans had average supercooling points between -24° and -26°C. Acclimation at -5°, 0° and 12°C for various time intervals had no significant effect on their ability to supercool. Glycerol was not found in specimens acclimated at -5° and 0°C. All specimens were killed by freezing at temperatures in the range of their supercooling points. Chill-coma temperatures of the collembolans were between -2° and -7°C.
Keywords: Bouvetøya; NARE 1976/77; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Lepidoptera - Viette, Pierre E L (Dybwad, 1952)
Publication Title: Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq., instituted and financed by consul Lars Christensen
Keywords: Antarktis; Possession Islands; Rosshavet; ekspedisjoner; forskning; hvalfangere; hvalfangst; virvelløse dyr; zoologi

Meeresstrand-Enchyträiden des südlichen Atlantischen Ozeans - Michaelsen, Wilhelm (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1935)
Keywords: Antarktis; Norvegia ekspedisjoner; børsteorm; enchytreer; forskning; virvelløse dyr; zoologi

Echinodermata from the Palmer Archipelago, South Shetland, South Georgia and the Bouvet Island : with description of new species of the moluscan genus Montacutas - Grieg, James A (Dybwad, 1929)
Publication Title: Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I
Keywords: Bouvetøya; biologi; ekspedisjoner; forskning; marinbiologi; pigghuder; virvelløse dyr